2018
DOI: 10.1158/1538-7445.sabcs17-pd3-11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD3-11: Efficacy and safety of subcutaneous or intravenous trastuzumab in patients with HER2-positive early breast cancer after 5 years' treatment-free follow-up: Final analysis from the phase III, open-label, randomized HannaH study

Abstract: Background HannaH (NCT00950300) compared subcutaneous and intravenous trastuzumab (H SC and H IV) as neoadjuvant–adjuvant therapy for HER2-positive breast cancer. The co-primary endpoints of pathological complete response (pCR) and serum trough concentration at predose cycle 8 demonstrated noninferiority between H SC and H IV. Efficacy analyses of event-free survival (EFS) and overall survival (OS) at a median follow-up of 40 months supported this noninferiority. Safety analyses also confirmed the consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Therefore, it is expected that the maximal clinical benefit will be achieved at these serum concentrations (with SC pertuzumab 600 mg). Because the approved IV pertuzumab regimen is assumed to saturate HER2 receptor binding, predicting maximum clinical efficacy with an SC pertuzumab dose with a noninferior C trough,ss should be appropriate; a noninferior C trough would ensure at least the same degree of target saturation as with IV administration and therefore ensure similar efficacy, as was seen with the development of both SC trastuzumab and SC rituximab …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is expected that the maximal clinical benefit will be achieved at these serum concentrations (with SC pertuzumab 600 mg). Because the approved IV pertuzumab regimen is assumed to saturate HER2 receptor binding, predicting maximum clinical efficacy with an SC pertuzumab dose with a noninferior C trough,ss should be appropriate; a noninferior C trough would ensure at least the same degree of target saturation as with IV administration and therefore ensure similar efficacy, as was seen with the development of both SC trastuzumab and SC rituximab …”
Section: Discussionmentioning
confidence: 99%
“…Fixed‐dose SC trastuzumab has a similar safety profile to that of IV trastuzumab and is noninferior in terms of pathologic complete response and C trough in patients with early breast cancer, supported by long‐term safety and efficacy results (6‐year event‐free survival and overall survival) in the HannaH (enHANced treatment with NeoAdjuvant Herceptin) study (NCT00950300). Similarly, the SABRINA (Subcutaneous Administration BRIdgiNg for PhAse 3) study (NCT01200758) showed that the SC formulation of rituximab had comparable efficacy and safety to the IV formulation and was demonstrated to be noninferior in terms of PK …”
mentioning
confidence: 98%
“…After a median follow-up of 12.2-12.4 months, the sc formulation was shown to be noninferior to the iv formulation, with pcr being 45.4% and 40.7% respectively (difference of 4.7%; 95% ci: 4.0% to 13.4%; noninferiority margin: -12.5%). Moreover, a 6-year follow-up analysis of the HannaH study showed noninferiority for the 6-year event-free survival and os rates, which were 65% and 84% for the two formulations respectively (event-free hazard ratio: 0.98; 95% ci: 0.74 to 1.29; os hazard ratio: 0.94; 95% ci: 0.61 to 1.45) 20 . In addition, all efficacy outcomes were consistent in the bodyweight subgroups 11,19 .…”
Section: Efficacymentioning
confidence: 96%